Digital Financial Literacy and Digital Finance Usage: A Systematic Literature Review and Bibliometric Analysis (Journal of Informatics Education and Research, 2025)
The accelerating integration of technology into financial services has transformed the global financial ecosystem, making digital financial services such as mobile banking, fintech platforms, and digital wallets essential in daily life. However, the effective use of these services depends significantly on individuals’ digital financial literacy (DFL), a competency that combines financial knowledge, digital skills, and cybersecurity awareness. This systematic literature review examines the relationship between DFL and digital finance usage (DFU). A total of 75 peer-reviewed articles published between 2010 and 2024 were analyzed following PRISMA guidelines. The review identifies four primary themes: conceptualization and measurement of DFL, determinants influencing DFU, barriers inhibiting effective usage, and the broader impact of DFL on financial inclusion and well-being. The findings highlight methodological inconsistencies, lack of standardized DFL measurement tools, geographical concentration in Asia and Africa, and insufficient exploration of emerging technologies such as blockchain and digital currencies. This review offers valuable insights for policymakers, financial institutions, educators, and technology developers, suggesting targeted interventions to bridge DFL gaps and promote financial inclusion. Future research directions are proposed, emphasizing the need for longitudinal studies, demographic-specific analyses, and integration of behavioral and psychological factors to develop a more cohesive and inclusive understanding of DFL in the digital economy.